Female Adherence Self-Efficacy before and after Couple HIV Testing and Counseling within Malawi’s Option B+ Program - Wesevich, Austin (AIDS Care, 2019)
Adherence self-efficacy, belief in one’s ability to adhere to daily medication, is strongly associated with antiretroviral therapy (ART) adherence and preventing mother-to-child HIV transmission. Couple-based interventions could enhance self-efficacy and adherence. We assessed the relationship between couple HIV testing and counseling (cHTC) and adherence self-efficacy using a 100-point culturally-adapted adherence self-efficacy scale (ASES). Secondarily, we explored the relationship between ASES and ART adherence. Ninety HIV-positive pregnant women at an antenatal clinic in Lilongwe, Malawi were enrolled in an observational cohort study. They were assessed with ASES immediately before and one month after receiving cHTC. Median ASES scores were 100 (IQR 95, 100) before and 100 (IQR 99, 100) after cHTC; there was a significant median difference (p=0.02) for participants before and after cHTC. This change in ASES scores was associated with the odds of self-reported ART adherence in the full population (OR 1.1, p=0.01), and there was a trend in the same direction for participants with imperfect baseline ASES scores (OR 1.1, p=0.2). In our population, adherence self-efficacy and ART adherence were both quite high, and those who had room to improve in self-efficacy may have benefited from cHTC, which in turn could impact ART adherence and ultimately mother-to-child transmission.